2016
DOI: 10.1007/s10120-016-0615-3
|View full text |Cite
|
Sign up to set email alerts
|

The Italian Research Group for Gastric Cancer (GIRCG) guidelines for gastric cancer staging and treatment: 2015

Abstract: This article reports the guidelines for gastric cancer staging and treatment developed by the GIRCG, and contains comprehensive indications for clinical management, including radiological, endoscopic, surgical, pathological, and oncological paths.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
117
2
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 156 publications
(130 citation statements)
references
References 55 publications
2
117
2
7
Order By: Relevance
“…In conclusion, the most recent guidelines suggest, in selected cases and in centers showing high volume and expertise, to take into consideration the dissection of distant nodes (especially periaortic nodes) (19,20). There is the need for a further RCT on this topic, comparing standard D2 and experimental D3 both in patients without and with evident nodal metastases in the periaortic area.…”
Section: Resultsmentioning
confidence: 99%
“…In conclusion, the most recent guidelines suggest, in selected cases and in centers showing high volume and expertise, to take into consideration the dissection of distant nodes (especially periaortic nodes) (19,20). There is the need for a further RCT on this topic, comparing standard D2 and experimental D3 both in patients without and with evident nodal metastases in the periaortic area.…”
Section: Resultsmentioning
confidence: 99%
“…However, we should underline that: (I) in such trial patients with clinical metastases to para-aortic nodes were not eligible for randomization; as such, the survival benefit of D2 plus was denied when performed with a "prophylactic" intent, but a potential benefit in patients with distant node metastases could not be excluded; (II) several observational and phase II studies reported longterm survivors in patients with metastases to para-aortic nodes, when treated by D2 plus lymphadenectomy; these rates were particularly high when surgery is preceded by neoadjuvant chemotherapy (30-33); (III) the incidence of distant lymph node metastases in Western patients has been estimated to be higher than Asian series, because it is related, besides T stage, to proximal tumor location and diffuse Lauren histotype (34); (IV) the JCOG 9501 compared patients treated by D2 vs. D2 plus the dissection, but the surgical difference between the two groups was the removal of para-aortic nodes, whereas "posterior" stations (8p, 12b/p, 13) were similarly dissected in the two groups under study; as such, in our opinion the conclusions of the study do not justify the exclusion of "posterior" lymphadenectomy from surgical guidelines. For all these reasons, the GIRCG guidelines advice D2 plus lymphadenectomy in patients at risk of lymph node metastases to "posterior" and para-aortic nodes (17). These can be identified in advanced forms located in proximal third, and advanced diffuse histotype in the distal third for para-aortic lymphadenectomy; the results of an observational GIRCG study for the identification of groups at risk of metastases to "posterior" stations are going to be published.…”
Section: D3 (D2 Plus) Lymphadenectomymentioning
confidence: 99%
“…Furthermore, in the West endoscopic resections, which can be considered as treatment but also staging procedures, are performed much less frequently than in East Asia, and the clinical diagnosis of lymph node metastasis by imaging procedures has still a low accuracy. As such, the GIRCG guidelines advise a standard D2 lymphadenectomy in early forms of GC (17). Only in selected cases (high-risk patients, early forms with favourable pathological characteristics, not treatable by endoscopic resections) more limited procedures should be considered (D1 plus).…”
Section: Lymphadenectomy For Early Formsmentioning
confidence: 99%
See 1 more Smart Citation
“…(6). However, the decision of Western surgeons to wait for significant results from clinical trials before changing their surgical behaviour, coupled with the refusal of eastern colleagues to perform D1 lymphadenectomy because they considered it inadequate, led to a delay of several years in the implementation of a clinical practice that is now recommended in almost all European National Guidelines (7)(8)(9)(10)(11). Interestingly, the European guidelines are not based on evidence-based medicine because no definitive trials have been conducted in this setting to date (12).…”
Section: Introductionmentioning
confidence: 99%